2018
DOI: 10.1002/ldr.3015
|View full text |Cite
|
Sign up to set email alerts
|

Tillage system change affects soil organic carbon storage and benefits land restoration on loess soil inNorthChina

Abstract: Soil organic carbon (SOC) is a core indicator of soil quality. A proper tillage system can improve SOC accumulation and benefit land restoration. This improvement is especially significant in loess soil, which is undergoing serious degradation in China. In this study, we chose a field that was used for crop production and used a traditional moldboard plow with crop residue removal (CT) for over 10 years. We then carried out a long-term field experiment (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 36 publications
2
14
1
Order By: Relevance
“…The maximum soil mass among the three tillage treatments at each soil depth was selected as a reference soil mass, therefore, the SOC stock of each treatment was only related to the SOC concentration. The SOC stocks under each treatment (NTF, STF, and PTF) after harvesting were lower than those before sowing in the 0–50 cm soil profile in this study, which was different from previous results where long-term continuous no tillage was beneficial to increasing SOC stocks [ 9 , 10 ]. By converting plow tillage to no tillage, the SOC stock may reach a new balance after 15–30 years in different regions [ 47 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The maximum soil mass among the three tillage treatments at each soil depth was selected as a reference soil mass, therefore, the SOC stock of each treatment was only related to the SOC concentration. The SOC stocks under each treatment (NTF, STF, and PTF) after harvesting were lower than those before sowing in the 0–50 cm soil profile in this study, which was different from previous results where long-term continuous no tillage was beneficial to increasing SOC stocks [ 9 , 10 ]. By converting plow tillage to no tillage, the SOC stock may reach a new balance after 15–30 years in different regions [ 47 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A twelve-year study in northeastern China showed that the SOC stock increased under no tillage but decreased under plow tillage compared to that under original soils [ 9 ]. Similarly, another experiment showed that the SOC stock in the 0–60 cm soil profile increased under no tillage with straw mulching and subsoiling with straw mulching compared with that under crop residue removal [ 10 ]. However, the SOC stock in the topsoil of southern Finland was lower after thirty years of reduced tillage than that under the conventional tillage, which may be related to the already high level of SOC concentration [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conservation tillage, especially no-tillage, results in accumulation of crop residues on the soil surface and reduces nutrient distribution in the soil profile [16]. Long-term no-tillage is reported to result in pronounced vertical stratification of soil nutrients, SOC, and other related soil properties [1,3,5,[17][18][19][20], which is otherwise distributed among soil layers in tilled soils [21]. No-tillage and reduced tillage upon conversion to conventional tillage will have a huge impact on SOC storage, nutrient uptake, and nutrient availability [10].…”
Section: Introductionmentioning
confidence: 99%
“…Land consolidation is commonly applied to paddy fields as a major measure to improve the physicochemical and biological properties of the soil. However, it is still unknown which land consolidation measures are most effective in improving soil quality (Wang et al, 2018b). Nonetheless, our research provides evidence that all land consolidation practices can alter the soil physicochemical and biological properties to improve soil quality in paddy fields.…”
Section: Discussionmentioning
confidence: 99%
“…Soil quality definition includes the physical, chemical and biological soil entities. Abiotic and biotic interaction, however, would easily be affected by land consolidation (Wang et al, 2018b; Zeng et al, 2018). Soil microbial communities play a critical role in organic matter (OM) decomposition and nutrient cycling of carbon, nitrogen and phosphorus.…”
Section: Introductionmentioning
confidence: 99%